A novel plant‑based approach for synthesis of iron oxide nanoparticles and cancer therapy - Soomro, Romesa; Abdelmonem, Mohamed; Meli, Abubakar Dantani; Panhwar, Motia; Che Abdullah, Che Azurahanim (Springer Science and Business Media LLC, 2025)
Cancer remains a major challenge in modern medicine, often hindered by the limitations of conventional treatments such as chemotherapy, including severe side effects and low specificity. Iron oxide nanoparticles (IONPs) have emerged as promising tools for cancer theranostics, owing to their magnetic responsiveness, tunable surface properties, and ability to enhance both therapeutic and diagnostic precision. This review focuses on the advancements in the green synthesis of IONPs using plant extracts rich in polyphenols, which serve as natural reducing agents while providing additional anti-cancer benefits. These green-synthesized IONPs demonstrate potential in targeted drug delivery, controlled release, and enhanced imaging through magnetic resonance imaging (MRI), offering a sustainable and effective approach to cancer treatment. The review highlights the biosafety, biocompatibility, and anticancer efficacy of green-synthesized IONPs through an in-depth analysis of preclinical in vitro studies from the last five years. Key challenges in plant-based synthesis, such as reproducibility and variability in phytochemical composition, are critically discussed alongside strategies to address these limitations. Furthermore, using waste materials in green synthesis is emphasized as a sustainable approach to nanoparticle production, promoting resource efficiency and environmental stewardship. This comprehensive analysis underscores the dual functionality of green-synthesized IONPs as a novel, eco-friendly solution for cancer theranostics, paving the way for sustainable and scalable applications in future biomedical research.